R, Symbolic Violence in Islamic Boarding school - Rahmi, Rahmi Diana; Fikri , Ahmad; Nurfadliyati, Nurfadliyati (Journal of Southeast Asian Islam and Society, 2024)
This Research aim the symbolic violence that occurs in favorite schools. When students from poor families given the opportunity to attend a school where the majority of students come from the upper class, students from the lower class will recognize many high class habitus. This is where the beginning of the occurrence of symbolic violence in schools. This study describes how poor students are carry out social interactions at school even though they have a different habitus from the habitus of the majority of students at school. School selected as the research location is a school dominated by upper class students in Malang City. Research using the method qualitatively by interviewing several poor students at the school. The results of the study show that some students feel inferior when it comes to interacting with rich students. They find it difficult to follow the habits of their friends who come from the upper class, for example: watching movies at the cinema, going to the mall, and more. Other students have an indifferent attitude and are not close to their friends different social class. The conclusion of the study states that inclusive schools accommodate students from many social groups Economics is a strategic effort to equalize learning opportunities. But on the other hand, when a school is dominated by students from upper class, then this condition is actually less profitable for poor students in that school.